Restoring Fertility: Excision of a Giant Ovarian Cyst in Women with Long-Standing Primary Infertility - Afdanil, Fitra; Nurkharisma, Isny Novia (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Ovarian cysts are common in women of reproductive age and can vary from simple functional cysts to large benign or malignant neoplasms. Giant ovarian cysts are rare and may contribute to infertility due to mechanical and hormonal disruptions. Objective: To report the diagnosis and management of a giant ovarian cyst in a young woman with long-standing primary infertility, emphasising the importance of individualised surgical planning for fertility preservation. Case presentation: A 26-year-old nulligravida woman presented with progressive abdominal distension over three months. Imaging showed a 22 cm cystic adnexal mass with suspicious features and elevated CA-125 (84 U/mL). The patient underwent exploratory laparotomy and bilateral salpingo-oophorectomy. Histopathological examination confirmed a benign serous cystadenoma. The patient recovered well and was referred for fertility counselling. Conclusions: Early evaluation and careful management of large ovarian cysts are crucial in reproductive-age women with infertility. Although tumor markers and imaging guide diagnosis, histopathology is definitive. Surgical decisions must balance oncologic safety and fertility potential to optimise patient outcomes.